Biology of the oldest butterfly species in the world, Baronia brevicornis: food, abundance, polymorphism, and survival - Ivette Galicia-Mendoza; Fernando Pineda-García; Ken Oyama; Adolfo Cordero-Rivera; Marcela Osorio-Beristain; Jorge Contreras-Garduño (Revista Mexicana de Biodiversidad)
The study of the basic biology of panchronic species could help understand their persistence through geological time. One of the least studied panchronic species is Baronia brevicornis Salvin (Lepidoptera: Papilionidae), the oldest known butterfly species endemic to Mexico. Here we report on our findings from studying a population of B. brevicornis in Sierra de Huautla, Morelos, for 3 years. In this population we identified 3 male and 3 female color morphs, making it perhaps the most complex polymorphism described yet for a panchronic species. We found a balanced sex ratio in newly emerged adults but a sex ratio biased to males at reproductive sites. Significantly, we found adults of the butterfly only on patches of the host plant Vachellia campechiana (Mill.) Seigler & Ebinger (Fabaceae) that also offered feeding sources for adults and report for the first-time adults feeding on 5 plant species. Additionally, differences in water use in trees of V. campechiana in zones with or without B. brevicornis suggest a relationship between butterfly food sources and plant water expenditure. Our findings on B. brevicornis could be used to develop conservation plans for this species.